Flux and strain in marriage contraction: The changing face of bridewealth in contemporary Ghana - Dodoo, N.D. (University of Ghana, 2019)
: Despite many changes in African societal structures, bridewealth still occupies a central role in contracting marriages. In Ghana, among married women aged 15 to 49, a nationally representative survey in 2014 reported that 82% were in marriages that involved bridewealth. I use semi-structured in-depth interviews with traditional rulers and community leaders in Ghana to examine the current role of bridewealth in marriage and the implications of changes in the practice of bridewealth for unions. The results reveal that social, cultural, and economic changes have led to a breakdown of norms surrounding marriage contraction and the marriage process being more expensive than it was in the past. These have given the leeway for women to contribute to the bridewealth payment, leading to a shift in the power base of marriage, which may lead to marital conflict and instability. It is suggested that the role of love in modern marriages is explored and men are engaged in the process of developing healthy masculinities as avenues to counter the effects of these changes in contracting marriage
Seminar
Keywords: African societal structures; bridewealth; marriages; masculinities